Review of At Work in the Iron Cage: The Prison as Gendered Organization. Dana M. Britton. Reviewed by Katherine van Wormer - Wormer, Katherine van (2005)
Book review of Dana M. Britton, At Work in the Iron Cage: The Prison as Gendered Organization. New York: New York University Press, 2003. $55.00 hardcover, $19.00 papercover